“AM I READY TO TEACH?”: EFL PRE-SERVICE TEACHERS’ MENTAL READINESS TO TEACH AND IMPLICATION FOR TEACHER EDUCATION - Anandari, Christina Lhaksmita; Suryaman, Maman; Basikin, Basikin (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
Third-year pre-service teachers in the English language education department in Indonesia may feel uncertain about their mental readiness to become English teachers. Although they have a high-intermediate level of English proficiency, they often fear facing the challenges of managing the class and showcasing mental readiness to become teachers. Therefore, this study explores the third-year Indonesian EFL pre-service teachers’ mental readiness to become teachers, and the need to emphasize mental readiness and grit to successful teaching practice. Twenty-three EFL pre-service teachers enrolled a microteaching course, as one of the teaching practice components in the English language education curriculum, participated in this study. They were asked to write structured reflections on their mental readiness, and their reflections were thoroughly examined using a narrative analysis. The results showed that the pre-service teachers expressed concern about their ability to manage the class and their students, which reflects their mental unreadiness to be the person in charge in the classroom. Moreover, the pre-service teachers highlighted the need to be more mentally aware of their attitude and grit in shaping their mental readiness to teach. This study contributes to a larger context-specific understanding of the roles of the English teacher education programs at the university level in assisting pre-service English teachers to achieve mental readiness and grit that can help them address the challenges.